THE MADINAH CHARTER, NOT A CONSTITUTION OF ISLAMIC STATE - ali romdhoni (TAWASUT, 2013)
This paper will state that Madinah Charter is not a constitutionthat is referred as the model in upholding islamic state. Usingsemiotic method, this paper will conclude that every dictumwithin the Madinah Charter has sort of code of conducts thatfunctions to provide social security within the Madinah societyat that time. Nevertheless, current politics could stillappropriate the fundamental values within the MadinahCharter especially in implementing justice-based governance,equality before the law, open public participation and so forth.Excessive intention of certain Muslim group, including inIndonesia, to uphold khilafah system is not in accordance withthe spirit of the Madinah charter. It is because the khilafah isbased on the monarchical system, which does not involve thepeople within the elections and so on as it is implied from theMadinah Charter.Keywords: the madinah charter, constitution, Islamic stateIntroduction